The application of two-dimensional fluorescence correlation spectroscopy on the interaction between bovine serum albumin and prulifloxacin. Issue 5 (2009) - Xue Xue, Mao-Yun Mao-Yun; Yang Yang, Ai-Ping Ai-Ping; Ma Ma, Mei-Hua Mei-Hua; Li Li, Xiao-Hua Xiao-Hua
Abstract : The interaction between bovine serum albumin (BSA) and prulifloxacin was investigated by ultraviolet spectrophotometer (UV) and fluorescence spectroscopy in this paper. Two-dimensional (2D) correlation spectroscopy was applied to the analysis of fluorescence spectra. The results of spectroscopic measurements suggested that prulifloxacin (PL) have a strong ability to quench the intrinsic fluorescence of bovine serum albumin through static quenching procedure. Thermodynamic parameter enthalpy changes (Δ H ) and entropy changes (Δ S ) were calculated. Owing to the spectral resolution enhancement in 2D correlation spectroscopy, the structure change of prulifloxacin can be observed.